Microfinance schemes and rural poverty alleviation in Zimbabwe: the case of Rotating Savings and Credit Association in Zvishavane - Breakfast, Valentine (Midlands State University, 2017)
The problem this study seeks to address is the effectiveness of ROSCA microfinance informal model poverty reduction. Zimbabwe has been experiencing economic decline and this has led to the aggressive adoption of social safety nets like Rotating Savings and Credit Associations by Non Governmental Organisations to cushion the rural households. The researcher purposed this research to evaluate the extent to which the ROSCA model is effective in preventing people from falling below the poverty line. The researcher adopted qualitative research approach making use of questionnaires and interviews so as to get to understand how poverty can be reduced by the ROSCA model. The researcher also put forward some theories to explain this phenomenon. Findings show that the ROSCA model has managed to transform the livelihood of the rural people thus it is effective in poverty reduction in Chenhunguru Ward 13. Furthermore, recommendations on the challenges noted were suggested by the researcher which would help for the much effective implementation of the model by policy makers or organisations.